Utilization of Maternal and Newborn Health Services in Gandaki Province, Nepal - Tantrika Raj Khanal; Govinda Prasad Devkota (The Journal of Aadikavi, 2026)
Geographic and service-access differences may have an effect on the use of maternal and neonatal health services in Gandaki Province, Nepal. In this study, prenatal care (ANC), delivery site, and postnatal check-up coverage were compared between urban and rural populations. A secondary descriptive analysis was conducted using data from the 2022 Nepal Demographic and Health Survey. In the first survey, a two-stage stratified cluster design was used. This study used the Gandaki Province subsample of 1,401 women aged 15 to 49 (409 rural and 992 urban). ANC visits, delivery locations, ANC provider type, and postnatal checkups were summarized using weighted frequencies and percentages. While 2.5% of rural women and none of the urban women reported no ANC visits, urban women (35.1%) and rural women (40.6%) reported four to seven ANC visits. While institutional delivery (public or private facility) was more common in urban areas (93.8% vs. 70.1%), home delivery was more common in rural areas (27.1% vs. 4.6%). Furthermore, compared to rural areas (66.5%), postnatal exams for women and infants were more prevalent in urban areas (74.8%). Lower combined postnatal check-up coverage and worse institutional delivery were the most evident rural disadvantages, even if a slightly higher percentage reported four to seven ANC visits. Gandaki Province should strengthen 24-hour delivery and postnatal care at remote birthing centers, prioritize referral transport for outlying villages, and send community health workers to follow up with mothers and newborns within 48 hours of delivery.